KEDUDUKAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG DALAM SISTEM KETATANEGARAAN INDONESIA SETELAH PERUBAHAN UNDANG-UNDANG DASAR 1945 DAN IMPLIKASI YURIDIS ATAS PENOLAKANNYA OLEH DEWAN PERWAKILAN RAKYAT - , IRWANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This legal research is library research, the library research is studying against each general principles of law, legal systematics, the synchronization level of law, legal history, and comparative law. The existence of field research functions as supporting data and answers certain problem formula. The point of this legal study is library research with a view to know the theories of law, hierarchy of legislation, the position of government regulation in lieu of law (Perpu), and juridical implications of its rejection by the house of representatives (DPR). This research uses several approaches of which is the approach of legislation, the historical approach, and the comparative approach. This research purposes to determine several things: the first, position of Perpu after the amendment of the 1945 constitution (UUD 1945), the second, juridical implications of rejection by the house of representative, the third, Perpu hierarchy before and after the amendment of the 1945 constitution, and the fourth, the consideration of the president before bring out Perpu. After doing this research, the writer have discovered some things: the first, the position of government regulation in lieu of law after the 1945 amendment is in accordance with the constitutional system of Indonesia namely presidential system, the material government regulation in lieu of law regulated in article 22 of the 1945 constitution has never undergone any changes, so the changes is thick with political interests between the executive and legislative branches, the second, juridical implications of government regulation in lieu of law rejected by the house representative is the revocation government regulation in lieu of law, so pass the regulation does not apply and the consequences can be determined by the house representative, the third, consideration of the president issued government regulation is a right guaranteed by the subjectivity of president and consideration due to external and internal factor governance. And the forth, the position of government regulation and legislation have in common in terms of substance but different in terms of shape and condition (time) of manufacture, there are still difference of opinion between legal experts and politic, therefore, government regulation in lieu of law be further clarified its position because the enforcement could be exceed government regulation in lieu of law products made by the parliament and the president, despite a temporary time in brackets.